Preparation and application of a three-dimensional porous hard carbon material
By preparing three-dimensional porous hard carbon materials, the problem of insufficient diffusion and cycle stability of the anode material of sodium ion battery is solved, the high specific capacity and cycle stability of sodium ion battery are achieved, and the application of sodium ion battery in a variety of energy storage and environment is expanded. possibility.
Patent Information
- Application Number
- CN202310165773.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-24
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-02-24
AI Technical Summary
The development of sodium ion battery anode materials is limited by the large radius of sodium ions, which makes it difficult for the carbonate electrolytes of existing materials to diffuse effectively in sodium-based anodes, limiting the application of graphite materials, and the cyclic stability of existing anode materials and insufficient capacity.
The preparation method of three-dimensional porous hard carbon materials is adopted to form a multi-layer hard carbon material with rich closed pore structure through high-temperature pre-carbonization of biomass materials, acid washing and impurities removal, etchant treatment, hole plugging agent addition and spray drying. , suitable for energy storage applications such as sodium ion batteries.
The prepared three-dimensional porous hard carbon material exhibits excellent electrochemical properties in sodium ion batteries, including high specific capacity and good cycle stability. It is suitable for lithium ion batteries, sodium ion batteries and other fields, and is also used in energy storage and environmental purification. There are broad application prospects in other aspects.
Smart Images

Figure CN116253311B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy storage materials, and specifically relates to the preparation and application of a three-dimensional porous hard carbon material. Background Art
[0002] In the past few years, there has been an industry trend to vigorously develop sodium-ion batteries (SIBs) technology, which operate at room temperature and are based on the concept of contrasting with lithium-ion batteries (LIBs). Currently, this technology will be based on the use of an organic electrolyte (usually a mixture of alkyl carbonate and sodium salt (generally NaPF6)) and two high-potential and low-potential electrodes that promote reversible redox reactions of sodium ions.
[0003] In the past few years, many SIBs cathode materials have been studied, including layered oxides, tunnel oxides, polyanion sodium salts, and Prussian blue analogs. However, the range of equally important anode materials is also very limited because the ionic radius of Na is very large ( The ionic radius of Li is ). Due to the large ionic radius of sodium, the carbonate electrolyte in the sodium-based anode cannot effectively diffuse into the graphite interlayer spacing (interlayer spacing is 0.335nm), so graphite materials cannot be used as widely as in lithium-ion batteries. Other anode materials have been widely studied, including non-graphitizable hard carbon (HC), alloys, oxides and organic compounds. Currently, HC materials with randomly oriented graphite layers are one of the most promising candidates for SIBs anode materials because of their high conductivity at 350mA hg -1 The high reversible capacity near Na / Na + The suitable average potential of HC materials is about 0.15 V, as well as their excellent cycling stability. In addition, the basic principles of the sodium storage mechanism in HC materials have also attracted widespread attention from researchers. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and application of a three-dimensional porous hard carbon material. The material used in the method is simple and low-cost, can provide excellent performance as an electrode material, and has broad application prospects.
[0005] In order to achieve the above invention object, the specific technical solution of the present invention is:
[0006] A method for preparing a three-dimensional porous hard carbon material comprises the following steps:
[0007] 1) Pre-carbonizing the biomass material at a certain heating rate under an inert atmosphere;
[0008] 2) washing the product obtained in step 1) with acid to remove impurities in the biomass material, filtering and cleaning it, and then drying it;
[0009] 3) dispersing the dried material in step 2) into deionized water, then adding an etchant, and heating the mixture on a heated magnetic stirrer until the water is completely dried;
[0010] 4) subjecting the substance obtained in step 3) to high-temperature pyrolysis at a certain heating rate under an inert atmosphere to obtain a porous hard carbon material;
[0011] 5) washing the porous hard carbon material obtained in step 4) with acid to remove excess impurities, filtering and cleaning, and then drying;
[0012] 6) dispersing the substance obtained in step 5) into a solution containing a certain amount of pore plugging agent and stirring;
[0013] 7) drying the material obtained in step 6) by spray drying;
[0014] 8) The material obtained in step 7) is subjected to high temperature treatment in an inert atmosphere at a certain heating rate to finally obtain a three-dimensional porous hard carbon material.
[0015] Furthermore, the biomass material described in step 1) is a biomass material with lignocellulose as the main component; including but not limited to walnut shell powder, almond shell powder, pecan shell powder, pine nut shell powder or macadamia shell powder; preferably, the biomass material is walnut shell powder with a particle size of 10±5μm.
[0016] Furthermore, in step 1), the temperature of the high temperature pyrolysis is 250-900° C., the pyrolysis time is 0.3-12 h, and the heating rate is 0.1-5° C. / min.
[0017] Furthermore, the acid used in step 2) and step 5) is hydrochloric acid, sulfuric acid or nitric acid, preferably hydrochloric acid; the purpose of cleaning is to remove metal ions, and an excess of acid is used in this application to ensure complete cleaning.
[0018] Furthermore, the etchant in step 3) is potassium hydroxide or sodium hydroxide, preferably potassium hydroxide; preferably, the mass ratio of the substance obtained in step (2) to the etchant is 1:0.5-3.
[0019] Furthermore, the heating temperature in step 3) is 60-160° C., and the heating time is not limited.
[0020] Furthermore, in step 4), the temperature of the high temperature pyrolysis is 500-1600° C., the pyrolysis time is 0.5-12 h, and the heating rate is 0.5-10° C. / min.
[0021] Furthermore, the pore plugging agent in step 6) is any one of resorcinol formaldehyde resin, phenolic resin, acrylic, ethyl α-cyanoacrylate and polyurethane; preferably, the pore plugging agent is phenolic resin.
[0022] Furthermore, the solution solvent in step 6) is methanol, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or ethylene glycol; preferably, the solvent is ethanol.
[0023] Furthermore, the stirring time in step 6) is 5-60 min.
[0024] Furthermore, the inlet air temperature of the spray drying in step 7) is 80-200°C.
[0025] Furthermore, the outlet air temperature of the spray drying in step 7) is 30-150°C.
[0026] Furthermore, the power of the fan for spray drying in step 7) is 10%-90%.
[0027] Furthermore, in step 7), the feed pump power of the spray drying is 10%-50%.
[0028] Furthermore, in step 8), the temperature of the high temperature pyrolysis is 700-1700° C., the pyrolysis time is 0.5-12 h, and the heating rate is 0.5-10° C. / min.
[0029] Another invention objective of the present application is to protect a three-dimensional porous hard carbon material obtained by adopting any one of the above technical solutions or any combination of the technical solutions.
[0030] The present invention also provides the application of the above three-dimensional porous hard carbon material in energy storage, such as for preparing a hard carbon anode for a sodium ion battery. The first efficiency of the activation process at 100mA / g is 76% and the specific capacity is 360mAh / g. At a current density of 1A / g, the specific capacity is 290mAh / g, indicating that the material has excellent electrochemical properties.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (I) In this method, an etchant is used to melt the wood cellulose in the biomass material to form interconnected pores. However, the interconnected pores are not conducive to the embedding / ejection of sodium ions. Subsequently, a pore-blocking agent is used to form a closed-pore structure, providing a better environment for the embedding and extraction of sodium ions.
[0033] (ii) The three-dimensional porous hard carbon material prepared by this method has good physical and chemical properties, unique pore structure and excellent conductivity due to its multi-layer and rich closed-pore structure, and can be better used in lithium-ion batteries, sodium-ion batteries, lithium / sodium-sulfur batteries, lithium / sodium-selenium batteries, aqueous batteries, air batteries, sensors, environmental purification, energy, catalysis and other important fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a SEM image of the hard carbon material obtained in Example 1;
[0035] Figure 2 The SEM image and mapping image of the hard carbon material obtained in Example 1;
[0036] Figure 3 The SEM image and mapping image of the hard carbon material obtained in Comparative Example 1;
[0037] Figure 4 TEM image of the hard carbon material obtained in Example 1;
[0038] Figure 5 The XPS graphs of the hard carbon materials obtained in Examples 1, 2, 3, 4, 5 and Comparative Examples 1 and 2;
[0039] Figure 6 XRD patterns of the hard carbon materials obtained in Examples 1, 2, 3, 4 and 5;
[0040] Figure 7 The XRD patterns of the hard carbon materials obtained in Comparative Examples 1 and 2;
[0041] Figure 8 The nitrogen adsorption-desorption curves of the hard carbon materials obtained in Example 1 and Comparative Example 2 are shown;
[0042] Fig. 9 This is a nitrogen adsorption-desorption curve diagram of potassium hydroxide in different proportions in Example 1;
[0043] Fig.10 The nitrogen adsorption-desorption curves of the hard carbon materials obtained in Examples 1, 2, 3, 4 and 5 are shown in Figure 1. The specific surface areas are 13.1, 18.6, 10.6, 11.3 and 12.6 m 2 / g;
[0044] Fig.11 The first cycle charge and discharge curves of the hard carbon materials obtained in Example 1 and Comparative Example 1;
[0045] Fig.12 The hard carbon obtained in Example 1 and Comparative Example 1 is 1A g -1 Cyclic curves under current density of ;
[0046] Fig.13 The charge and discharge curves of the hard carbon obtained in Example 1 at different numbers of cycles at a current density of 1 A / g;
[0047] Table 5 is a comparison table of the electrochemical performance of Examples 1, 2, 3, 4, 5 and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0048] In order to make the content of the present invention easier to understand, the process described in the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments.
[0049] In the following examples, the inert atmosphere described is argon atmosphere. The reagents used in this application are all commercially available products.
[0050] Embodiment 1:
[0051] A method for preparing a three-dimensional porous hard carbon material comprises the following steps:
[0052] (1) Using dried walnut shell powder (particle size of 10±5 μm) as biomass material, the biomass material is pyrolyzed at 500°C in an inert atmosphere for 0.8 h at a heating rate of 1.5°C / min to obtain a hard carbon material converted from biomass;
[0053] (2) The obtained product was dispersed in 50 mL of deionized water and 10 mL of 12 M hydrochloric acid was added dropwise to wash away impurities. Then, the mixture was filtered and washed until neutral, and dried at 50 ° C to remove surface moisture;
[0054] (3) dispersing the product obtained in step (2) into deionized water, and then adding potassium hydroxide, wherein the mass ratio of the product obtained in step (2) to potassium hydroxide is 1:2, and then transferring the material to a heating stirrer, heating and stirring at 80° C. until the water evaporates;
[0055] (4) pyrolyzing the product obtained in step (3) at 600° C. in an inert atmosphere for 3 hours at a heating rate of 3° C. / min to obtain a hard carbon material;
[0056] (5) Disperse the hard carbon material obtained in step (4) in 50 mL of deionized water, and drop 10 mL of 12 M hydrochloric acid to wash away impurities. Then filter and wash until neutral, and dry at 50 °C;
[0057] (6) 500 mg of resorcinol formaldehyde resin was dissolved in 100 ml of ethanol, and 500 mg of the substance obtained in step (5) was added thereto. The mixture was stirred for 10 minutes on a magnetic stirrer. Then, 50 mL of deionized water was added to the solution and the stirring was continued for 10 minutes to form a uniform solution.
[0058] (7) The ethanol and deionized water in the solution are then removed by spray drying and the powder is collected.
[0059] (8) The dried product was pyrolyzed at 1200°C in an inert atmosphere for 3 h at a heating rate of 3°C / min to obtain a three-dimensional porous hard carbon material.
[0060] The hard carbon material was prepared by the same method and steps as in Example 1, except that the resorcinol formaldehyde resin was replaced by phenolic resin, acrylic, ethyl α-cyanoacrylate and polyurethane. The properties exhibited are shown in Table 1.
[0061] Table 1:
[0062]
[0063] The hard carbon material was prepared by the same method and steps as in Example 1, except that potassium hydroxide was replaced by zinc chloride and sodium hydroxide, respectively. The properties exhibited are shown in Table 2.
[0064] Table 2
[0065]
[0066] The hard carbon material was prepared by the same method and steps as in Example 1, except that the mass ratio of the material to potassium hydroxide was changed to 1:0.5, 1:1 and 1:3. The properties exhibited are shown in Table 3.
[0067] Table 3
[0068]
[0069] Embodiment 2:
[0070] A method for preparing a three-dimensional porous hard carbon material comprises the following steps:
[0071] (1) Using dried almond shell powder (particle size of 10±5 μm) as a biomass material, and then pyrolyzing the dried almond shell powder at 500°C in an inert atmosphere for 0.8 h at a heating rate of 1.5°C per minute to obtain a hard carbon material converted from biomass;
[0072] (2) Disperse the hard carbon material converted from biomass in 50 mL of deionized water and drop 10 mL of 12 M hydrochloric acid to wash away impurities. Then filter and wash until neutral, and dry at 50 °C;
[0073] (3) dispersing the product obtained in step (2) into deionized water, then adding potassium hydroxide, wherein the mass ratio of the product obtained in step (2) to potassium hydroxide is 1:2, and transferring the mixture to a heating stirrer and heating and stirring at 80° C. until the water evaporates;
[0074] (4) pyrolyzing the product of step (3) at 600° C. in an inert atmosphere for 3 hours at a heating rate of 3° C. per minute to obtain a hard carbon material;
[0075] (5) Disperse the product obtained in step (4) in 50 mL of deionized water and drop 10 mL of 12 M hydrochloric acid to wash away impurities. Then filter and wash until neutral, and dry at 50°C;
[0076] (6) Dissolve 500 mg of resorcinol formaldehyde resin in 100 ml of ethanol, then add 500 mg of the hard carbon obtained in step (5) and stir for 10 minutes using a magnetic stirrer. Then, add 50 mL of deionized water to the solution and continue stirring for 10 minutes to form a uniform solution.
[0077] (7) The ethanol and deionized water in the solution are then removed by spray drying and the powder is collected.
[0078] (8) The dried product was pyrolyzed at 1200°C in an inert atmosphere for 3 hours at a heating rate of 3°C per minute to obtain a three-dimensional porous hard carbon material.
[0079] Embodiment 3:
[0080] A method for preparing a three-dimensional porous hard carbon material comprises the following steps:
[0081] (1) Using dried pecan husk powder (particle size of 10±5 μm) as biomass material, the dried pecan husk powder was pyrolyzed at 500°C in an inert atmosphere for 0.8 h at a heating rate of 1.5°C per minute to obtain a hard carbon material converted from biomass;
[0082] (2) Disperse the hard carbon material converted from biomass in 50 mL of deionized water and drop 10 mL of 12 M hydrochloric acid to wash away impurities. Then filter and wash until neutral, and dry at 50 °C;
[0083] (3) dispersing the product obtained in step (2) into deionized water, adding potassium hydroxide in a mass ratio of 1:2, and transferring the mixture to a heating stirrer and heating and stirring at 80° C. until the water evaporates;
[0084] (4) pyrolyzing the product of step (3) at 600° C. in an inert atmosphere for 3 hours at a heating rate of 3° C. per minute to obtain a hard carbon material;
[0085] (5) Disperse the product obtained in step (4) in 50 mL of deionized water and drop 10 mL of 12 M hydrochloric acid to wash away impurities. Then filter and wash until neutral, and dry at 50°C;
[0086] (6) Dissolve 500 mg of resorcinol formaldehyde resin in 100 ml of ethanol and add 500 mg of the hard carbon obtained in step (5). Stir for 10 minutes using a magnetic stirrer. Then, add 50 mL of deionized water to the solution and continue stirring for 10 minutes to form a uniform solution.
[0087] (7) The ethanol and deionized water in the solution are then removed by spray drying and the powder is collected.
[0088] (8) The dried product was pyrolyzed at 1200°C in an inert atmosphere for 3 hours at a heating rate of 3°C per minute to obtain a three-dimensional porous hard carbon material.
[0089] Embodiment 4:
[0090] A method for preparing a three-dimensional porous hard carbon material comprises the following steps:
[0091] (1) Using dried pine nut shell powder (particle size of 10±5 μm) as a biomass material, the dried pine nut shell powder is then pyrolyzed at 500°C in an inert atmosphere for 0.8 h at a heating rate of 1.5°C per minute to obtain a hard carbon material converted from biomass;
[0092] (2) Disperse the product obtained in step (1) in 50 mL of deionized water and drop 10 mL of 12 M hydrochloric acid to wash away impurities. Then filter and wash until neutral, and dry at 50°C;
[0093] (3) dispersing the product obtained in step (2) into deionized water, adding potassium hydroxide in a mass ratio of 1:2, and transferring the mixture to a heating stirrer and heating and stirring at 80° C. until the water evaporates;
[0094] (4) pyrolyzing the product obtained in step (3) at 600° C. in an inert atmosphere for 3 hours at a heating rate of 3° C. per minute to obtain a hard carbon material;
[0095] (5) Disperse the product obtained in step (4) in 50 mL of deionized water and drop 10 mL of 12 M hydrochloric acid to wash away impurities. Then filter and wash until neutral, and dry at 50°C;
[0096] (6) Dissolve 500 mg of resorcinol formaldehyde resin in 100 ml of ethanol and add 500 mg of the hard carbon obtained in step (5). Stir for 10 minutes using a magnetic stirrer. Then, add 50 mL of deionized water to the solution and continue stirring for 10 minutes to form a uniform solution.
[0097] (7) The ethanol and deionized water in the solution are then removed by spray drying and the powder is collected.
[0098] (8) The dried product was pyrolyzed at 1200°C in an inert atmosphere for 3 hours at a heating rate of 3°C per minute to obtain a three-dimensional porous hard carbon material.
[0099] Embodiment 5:
[0100] A method for preparing a three-dimensional porous hard carbon material comprises the following steps:
[0101] (1) Using dried macadamia nut shell powder (particle size of 10±5 μm) as the biomass material, the dried macadamia nut shell powder is then pyrolyzed at 500°C in an inert atmosphere for 0.8 h at a heating rate of 1.5°C per minute to obtain a hard carbon material converted from biomass;
[0102] (2) Disperse the product obtained in step (1) in 50 mL of deionized water and drop 10 mL of 12 M hydrochloric acid to wash away impurities. Then filter and wash until neutral, and dry at 50°C;
[0103] (3) dispersing the product obtained in step (2) into deionized water, adding potassium hydroxide in a mass ratio of 1:2, and transferring the mixture to a heating stirrer and heating and stirring at 80° C. until the water evaporates;
[0104] (4) pyrolyzing the product obtained in step (3) at 600° C. in an inert atmosphere for 3 hours at a heating rate of 3° C. per minute to obtain a hard carbon material;
[0105] (5) Disperse the product obtained in step (4) in 50 mL of deionized water and drop 10 mL of 12 M hydrochloric acid to wash away impurities. Then filter and wash until neutral, and dry at 50°C;
[0106] (6) Dissolve 500 mg of resorcinol formaldehyde resin in 100 ml of ethanol, add 500 mg of the hard carbon obtained in step (5), stir for 10 minutes with a magnetic stirrer, then add 50 mL of deionized water to the solution, and continue stirring for 10 minutes to form a uniform solution.
[0107] (7) The ethanol and deionized water in the solution are then removed by spray drying and the powder is collected.
[0108] (8) The dried product was pyrolyzed at 1200°C in an inert atmosphere for 3 hours at a heating rate of 3°C per minute to obtain a three-dimensional porous hard carbon material.
[0109] Comparative Example 1:
[0110] The one-step method for preparing biomass hard carbon material is prepared according to the following steps:
[0111] Walnut shell powder (particle size of 10±5 μm) was pyrolyzed at 1200°C in an inert atmosphere for 3 hours at a heating rate of 3°C per minute to obtain a hard carbon material.
[0112] Comparative Example 2:
[0113] (1) pyrolyzing dried walnut shell powder (particle size of 10±5 μm) at 500°C in an inert atmosphere for 0.8 h at a heating rate of 1.5°C per minute to obtain a hard carbon material converted from biomass;
[0114] (2) Disperse the product obtained in step (1) in 50 mL of deionized water and drop 10 mL of 12 M hydrochloric acid to wash away impurities. Then filter and wash until neutral, and dry at 50°C;
[0115] (3) dispersing the product obtained in step (2) into deionized water, adding potassium hydroxide in a mass ratio of 1:2, and transferring the mixture to a heating stirrer and heating and stirring at 80° C. until the water evaporates;
[0116] (4) pyrolyzing the product of step (3) at 600° C. in an inert atmosphere for 3 hours at a heating rate of 3° C. per minute to obtain a hard carbon material;
[0117] (5) The product obtained in step (4) was dispersed in 50 mL of deionized water and 10 mL of 12 M hydrochloric acid was added dropwise to wash away impurities. The product was then filtered and washed until neutral, and dried at 50°C.
[0118] Comparative Example 3:
[0119] The hard carbon material was prepared by the same method and steps as in Example 1, except that potassium hydroxide was replaced by calcium hydroxide, potassium permanganate, nickel hydroxide and cobalt hydroxide. The properties exhibited are shown in Table 4.
[0120] Table 4:
[0121]
[0122] experiment:
[0123] The hard carbon materials prepared in Examples 1, 2, 3, 4, and 5 and the materials prepared in Comparative Examples 1, 2, and 3 were respectively made into negative electrodes for sodium ion batteries and relevant performance tests were performed.
[0124] Take the materials obtained in Examples 1, 2, 3, 4, 5 and Comparative Examples 1, 2, 3 and mix them with PVDF binder in a mass ratio of 90:10, then add an appropriate amount of NMP, grind them into a paste in an agate mortar, and apply them on an aluminum current collector. The coating mass is about 2.5 mg of electrode active material. Then the electrode is vacuum dried at 120°C for 12 hours to obtain a sodium ion battery negative electrode. Sodium metal is used as the positive electrode, the electrolyte is NaPF6in EC+DMC (vol%: 1:1), and the voltage range is 0.01-3V. The charge and discharge tester is Land CT2001A. The specific results are shown in Table 5.
[0125] Table 5 Comparison of electrochemical performance of Examples 1, 2, 3, 4, 5 and Comparative Examples 1, 2:
[0126]
[0127] Figure 1 This is a SEM image of the hard carbon material obtained in Example 1. From the low-magnification SEM image, it can be seen that the material is rod-shaped and has a rough surface, accompanied by the appearance of voids.
[0128] Figure 2 The SEM image and mapping image of the hard carbon material obtained in Example 1. It can be seen that the material is mainly composed of two elements, C and O.
[0129] Figure 3 The SEM image and mapping image of the hard carbon material obtained in Comparative Example 1. It can be seen that the surface of the material is rough and irregular, and is mainly composed of two elements, C and O.
[0130] Figure 4 This is a TEM image of the hard carbon material obtained in Example 1. From the transmission electron microscope image, it can be seen that the lamellae are very thin and have abundant micropores and mesopores. At the same time, disordered lattice gaps of hard carbon can be observed.
[0131] Figure 5 The XPS graphs of the materials obtained in Examples 1, 2, 3, 4, 5 and Comparative Examples 1 and 2 show that only C and O elements are present in the materials.
[0132] Figure 6 The XRD patterns of the materials obtained in Examples 1, 2, 3, 4 and 5 are shown in Table 1. The broad diffraction peak at about 20 degrees shows that the obtained material is a hard carbon material, and no other impurity peaks are detected.
[0133] Figure 7 The XRD patterns of the materials obtained in Comparative Examples 1 and 2 are shown. From the broad diffraction peak at about 20 degrees, it can be seen that the obtained materials are hard carbon materials, and no other impurity peaks are detected.
[0134] Figure 8 The nitrogen adsorption-desorption curves of the materials obtained in Example 1 and Comparative Example 2 are shown in FIG. 1. The specific surface area of Example 1 is 13.1 m 2 / g, the specific surface area of comparative example 1 is 1128.5m 2 / g. It can be seen from the figure that the material has abundant micropores before pore blocking, which can provide an effective ion transmission path for the transmission of sodium ions. After pore blocking, the specific surface area drops sharply, forming a more favorable closed-pore structure.
[0135] Fig. 9 The nitrogen adsorption and desorption curves of potassium hydroxide in different ratios in Example 1 are shown in Figure 1. The specific surface areas of 1:0.5-1:3 are 5.3, 12.6, 13.1 and 15.1 m 2 / g.
[0136] Fig.10 The nitrogen adsorption-desorption curves of the hard carbon materials obtained in Examples 1, 2, 3, 4 and 5 are shown in Figure 1. The specific surface areas are 13.1, 18.6, 10.6, 11.3 and 12.6 m 2 / g.
[0137] Fig.11 The first cycle charge and discharge curves of the hard carbon materials obtained in Example 1 and Comparative Example 1. As can be seen from the figure, at the same current density, Comparative Example 1 has no obvious platform, while Example 1 begins to have a platform at around 0.1V and provides a higher capacity.
[0138] Fig.12 The hard carbon obtained in Example 1 and Comparative Example 1 is 1A g -1 Cyclic curves at a current density of . As can be seen from the figure, during the activation process of 100mA / g, the first efficiency of Comparative Example 1 is 55.9% and the capacity is 143mAh / g, while the first efficiency of Example 1 is 76% and the specific capacity is 360mAh / g. At a current density of 1A / g, the capacity of Comparative Example 1 is 88mAh / g, and the capacity of Example 1 is 290mAh / g, indicating that the material has good electrochemical properties.
[0139] Fig.13 The charge and discharge curves of the hard carbon obtained in Example 1 at different cycle numbers at a current density of 1 A / g are shown in the figure. It can be seen from the figure that the material has good cycle stability.
[0140] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A method for preparing a three-dimensional porous hard carbon material, Features The following steps are involved: 1) The biomass material powder is subjected to high-temperature pre-carbonization at a certain heating rate under an inert atmosphere; the high-temperature pre-carbonization temperature is 250~900℃, the high-temperature pre-carbonization time is 0.3~12h, and the heating rate is 0.1~5℃ / min; 2) washing the substance obtained in step (1) with acid to remove impurities in the biomass waste, filtering and cleaning it, and then drying it; 3) Dispersing the substance obtained in step (2) into deionized water, then adding an etchant, and heating on a heated magnetic stirrer until the water is completely dried; the etchant is potassium hydroxide or sodium hydroxide; the mass ratio of the substance obtained in step (2) to the etchant is 1:2-3; 4) subjecting the substance obtained in step (3) to high-temperature pyrolysis at a certain heating rate under an inert atmosphere to obtain a porous hard carbon material; 5) washing the porous hard carbon material obtained in step (4) with acid to remove excess impurities, filtering and cleaning, and then drying; 6) dispersing the substance obtained in step (5) into a solution containing a certain amount of a pore-blocking agent and stirring the solution; the pore-blocking agent is resorcinol formaldehyde resin; the stirring time is 5-60 minutes; the mass ratio of the substance obtained in step (5) to the pore-blocking agent is 1:1; 7) Drying the substance obtained in step (6) by spray drying; 8) The material obtained in step (7) is subjected to high temperature treatment in an inert atmosphere at a certain heating rate to finally obtain a three-dimensional porous hard carbon material.
2. The method for preparing the three-dimensional porous hard carbon material according to claim 1, Features: The biomass material in step 1) is walnut shell powder, almond shell powder, pecan shell powder, pine nut shell powder or macadamia shell powder.
3. The method for preparing the three-dimensional porous hard carbon material according to claim 1, Features: The acids in step 2) and step 5) are hydrochloric acid, sulfuric acid or nitric acid.
4. The method for preparing the three-dimensional porous hard carbon material according to claim 1, Features: The heating temperature in step 3) is 60-160°C.
5. The method for preparing the three-dimensional porous hard carbon material according to claim 1, Features: In the step 4), the temperature of the high temperature pyrolysis is 500-1600° C., the pyrolysis time is 0.5-12 h, and the heating rate is 0.5-10° C. / min.
6. The method for preparing the three-dimensional porous hard carbon material according to claim 1, Features: The solvent in the solution in step 6) is methanol, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or ethylene glycol.
7. The method for preparing the three-dimensional porous hard carbon material according to claim 1, Features: In step 7), the inlet air temperature of the spray drying is 80-200°C; the outlet air temperature of the spray drying is 30-150°C; the fan power of the spray drying is 10%-90%; and the feed pump power of the spray drying is 10%-50%.
8. The method for preparing the three-dimensional porous hard carbon material according to claim 1, Features: In the step 8), the temperature of the high temperature pyrolysis is 700-1700° C., the pyrolysis time is 0.5-12 h, and the heating rate is 0.5-10° C. / min.
9. A three-dimensional porous hard carbon material prepared by the method according to any one of claims 1 to 8.
10. Use of the three-dimensional porous hard carbon material as claimed in claim 9, Features: The three-dimensional porous hard carbon material is used as an anode material for sodium ion batteries.
Citation Information
Patent Citations
Hard carbon material for anode of sodium-ion battery, preparation method of hard carbon material and related sodium-ion battery
CN109678130A
Nanocarbon material composite biomass hard carbon electrode material and preparation method and application thereof
CN113044827A
Hard carbon negative electrode material and preparation method thereof, negative electrode plate and sodium ion battery
CN115557486A
